Membangun Desa Wisata Berbasis Kapasitas SDM: Studi Pengaruh Kualitas Manusia dalam Pengembangan Desa Tipang, Humbang Hasundutan - Nova Bernedeta Sitorus; Cindy Kahirunisa Marpaung; Jul Indah Sulistriani Laia; Loly Surya Sirait; Putriani Br Sinamo (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
This study investigates the impact of human resource capacity on the development of Tipang Tourism Village in Humbang Hasundutan Regency, Indonesia. Despite its outstanding natural and cultural potential—recognized nationally as a leading tourism village—Tipang still faces challenges in achieving sustainable development, particularly due to limited skills, knowledge, and community awareness. Strengthening human resource capacity is therefore essential to fostering professional, creative, and sustainable tourism management. Adopting a quantitative approach, the study gathered data through questionnaires, interviews, direct observations, and literature review. The sample comprised local residents and tourists selected representatively. Data analysis used descriptive statistics and simple regression via SPSS. Results show a significant influence of human resource capacity on tourism development, supported by an F-value of 11.636 (greater than the F-table value of 3.18) and a t-value of 3.411 (greater than the t-table value of 1.677). The R² value of 19.5% suggests a moderate contribution, highlighting the importance of community competence in advancing sustainable tourism. The study recommends enhanced tourism-related training and education for local communities and encourages further research incorporating additional variables for broader insights.